Effects of e-training approach on Omani teachers' Adobe Photoshop knowledge and their attitudes toward e-training [electronic resource] - Suleiman Mohammed Nasser Al-Amri, 1971- (2011)
Thesis (Ph.D (Teknologi Pendidikan)) - Universiti Teknologi Malaysia, 2011